Signal processing for 5G : algorithms and implementations - Luo, Fa-Long; Zhang, Charlie (Chichester, West Sussex, United Kingdom : Wiley, 2016)
Fa-Long Luo, Ph.D., IEEE Fellow Charlie Zhang, Ph.D., IEEE Fellow A comprehensive and invaluable guide to 5G technology, implementation and practice in one single volume. For all things 5G, this book is a must-read. Signal processing techniques have played the most important role in wireless communications since the second generation of cellular systems. It is anticipated that new techniques employed in 5G wireless networks will not only improve peak service rates significantly, but also enhance capacity, coverage, reliability , low-latency, efficiency, flexibility, compatibility and convergence to meet the increasing demands imposed by applications such as big data, cloud service, machine-to-machine (M2M) and mission-critical communications. This book is a comprehensive and detailed guide to all signal processing techniques employed in 5G wireless networks. Uniquely organized into four categories, New Modulation and Coding, New Spatial Processing, New Spectrum Opportunities and New System-level Enabling Technologies, it covers everything from network architecture, physical-layer (down-link and up-link), protocols and air interface, to cell acquisition, scheduling and rate adaption, access procedures and relaying to spectrum allocations. All technology aspects and major roadmaps of global 5G standard development and deployments are included in the book. Key Features: . Offers step-by-step guidance on bringing 5G technology into practice, by applying algorithms and design methodology to real-time circuit implementation, taking into account rapidly growing applications that have multi-standards and multi-systems. . Addresses spatial signal processing for 5G, in particular massive multiple-input multiple-output (massive-MIMO), FD-MIMO and 3D-MIMO along with orbital angular momentum multiplexing, 3D beamforming and diversity.. Provides detailed algorithms and implementations, and compares all multicarrier modulation and multiple access schemes that offer superior data transmission performance including FBMC, GFDM, F-OFDM, UFMC, SEFDM, FTN, MUSA, SCMA and NOMA.. Demonstrates the translation of signal processing theories into practical solutions for new spectrum opportunities in terms of millimeter wave, full-duplex transmission and license assisted access. . Presents well-designed implementation examples, from individual function block to system level for effective and accurate learning. . Covers signal processing aspects of emerging system and network architectures, including ultra-dense networks (UDN), software-defined networks (SDN), device-to-device (D2D) communications and cloud radio access network (C-RAN).
MODULATION, CODING AND WAVEFORM FOR 5G. An Introduction to Modulations and Waveforms for 5G Networks / Stefano Buzzi, Alessandro Ugolini, Alessio Zappone, Giulio Colavolpe -- Faster-than-Nyquist Signaling for 5G Communication / John B Anderson -- From OFDM to FBMC: Principles and Comparisons / Wei Jiang, Thomas Kaiser -- Filter Bank Multicarrier for Massive MIMO / Arman Farhang, Nicola Marchetti, Behrouz Farhang-Boroujeny -- Bandwidth-compressed Multicarrier Communication: SEFDM / Izzat Darwazeh, Tongyang Xu, Ryan C Grammenos -- Non-orthogonal Multi-User Superposition and Shared Access / Yifei Yuan -- Non-Orthogonal Multiple Access (NOMA): Concept and Design / Anass Benjebbour, Keisuke Saito, Anxin Li, Yoshihisa Kishiyama, Takehiro Nakamura -- Major 5G Waveform Candidates: Overview and Comparison / Hao Lin, Pierre Siohan -- NEW SPATIAL SIGNAL PROCESSING FOR 5G. Massive MIMO for 5G: Theory, Implementation and Prototyping / Ove Edfors, Liang Liu, Fredrik Tufvesson, Nikhil Kundargi, Karl Nieman -- Millimeter-Wave MIMO Transceivers: Theory, Design and Implementation / Akbar M Sayeed, John H Brady -- 3D Propagation Channels: Modeling and Measurements / Andreas F Molisch -- 3D-MIMO with Massive Antennas: Theory, Implementation and Testing / Guangyi Liu, Xueying Hou, Fei Wang, Jing Jin, Hui Tong -- Orbital Angular Momentum-based Wireless Communications: Designs and Implementations / Alan E Willner, Yan Yan, Yongxiong Ren, Nisar Ahmed, Guodong Xie -- NEW SPECTRUM OPPORTUNITIES FOR 5G. Millimeter Waves for 5G: From Theory To Practice / Malik Gul, Eckhard Ohlmer, Ahsan Aziz, Wes McCoy, Yong Rao -- *5G Millimeter-wave Communication Channel and Technology Overview / Li Qian (Clara), Jung Hyejung, Zong Pingping, Wu Geng -- General Principles and Basic Algorithms for Full-duplex Transmission / Thomas Kaiser, Nidal Zarifeh -- Design and Implementation of Full-duplex Transceivers / Katsuyuki Haneda, Mikko Valkama, Taneli Riihonen, Emilio Antonio-Rodriguez, Dani Korpi -- NEW SYSTEM-LEVEL ENABLING TECHNOLOGIES FOR 5G. Cloud Radio Access Networks: Uplink Channel Estimation and Downlink Precoding / Osvaldo Simeone, Jinkyu Kang, Joonkhyuk Kang, Shlomo Shamai (Shitz) -- Energy-efficient Resource Allocation in 5G with Application to D2D / Alessio Zappone, Francesco Di Stasio, Stefano Buzzi, Eduard Jorswieck -- Ultra Dense Networks: General Introduction and Design Overview / Jianchi Zhu, Xiaoming She, Peng Chen -- Radio-resource Management and Optimization in 5G Networks / Antonis Gotsis, Athanasios Panagopoulos, Stelios Stefanatos, Angeliki Alexiou -- REFERENCE DESIGN AND 5G STANDARD DEVELOPMENT. Full-duplex Radios in 5G: Fundamentals, Design and Prototyping / Jaeweon Kim, Min Soo Sim, MinKeun Chung, Dong Ku Kim, Chan-Byoung Chae -- 5G Standard Development: Technology and Roadmap / Juho Lee, Yongjun Kwak.
Includes bibliographical references and index.
Print version record.
Keywords: Signal processing -- Digital techniques -- Mathematics; Mobile communication systems -- Standards; Wireless communication systems -- Standards; Computer algorithms; TECHNOLOGY & ENGINEERING / Mechanical; Computer algorithms; Mobile communication systems -- Standards; Signal processing -- Digital techniques -- Mathematics; Wireless communication systems -- Standards; Electronic books; Electronic books